2008
DOI: 10.1037/0021-9010.93.3.674
|View full text |Cite
|
Sign up to set email alerts
|

"Did you have a nice evening?" A day-level study on recovery experiences, sleep, and affect.

Abstract: In this study, the authors used a within-person design to examine the relation between recovery experiences (psychological detachment, relaxation, mastery experiences) during leisure time, sleep, and affect in the next morning. Daily survey data gathered over the course of 1 work week from 166 public administration employees analyzed with a hierarchical linear modeling approach showed that low psychological detachment from work during the evening predicted negative activation and fatigue, whereas mastery exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

42
693
8
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 670 publications
(755 citation statements)
references
References 80 publications
42
693
8
12
Order By: Relevance
“…Yet, the theoretical and empirical mindfulness literature suggests that mindfulness does not only have trait-like but also state-like properties (Glomb et al, 2011;Weinstein et al, 2009) and so does sleep quality (Rook & Zijlstra, 2006;Sonnentag et al, 2008;Sonnentag & Binnewies, 2013;Walkowiak, Hülsheger, & Zijlstra, 2010. Indeed, day-to-day within-person variation in mindfulness has been shown to be substantial, ranging between 38% and 71% (Brown & Ryan, 2003;Hülsheger et al, 2013).…”
Section: Mindfulness and Sleep Quality From A Day-level Perspectivementioning
confidence: 99%
See 1 more Smart Citation
“…Yet, the theoretical and empirical mindfulness literature suggests that mindfulness does not only have trait-like but also state-like properties (Glomb et al, 2011;Weinstein et al, 2009) and so does sleep quality (Rook & Zijlstra, 2006;Sonnentag et al, 2008;Sonnentag & Binnewies, 2013;Walkowiak, Hülsheger, & Zijlstra, 2010. Indeed, day-to-day within-person variation in mindfulness has been shown to be substantial, ranging between 38% and 71% (Brown & Ryan, 2003;Hülsheger et al, 2013).…”
Section: Mindfulness and Sleep Quality From A Day-level Perspectivementioning
confidence: 99%
“…Psychological detachment in turn is related to sleep quality. Researchers have argued that insufficient detachment from work and rumination during non-work time causes a mental continuation of work demands and work stressors and thereby impedes successful recovery (Querstret & Cropley, 2012;Sonnentag et al, 2008). This results in continued psychophysiological activation during non-work time that hinders sleep (Querstret & Cropley, 2012).…”
Section: The Mediating Role Of Psychological Detachmentmentioning
confidence: 99%
“…Activities such as listening to music or taking a walk can be initiated deliberately by the person to achieve this state (Sonnentag & Fritz, 2007). Sonnentag, Binnewies, and Mojza (2008) have shown that relaxation in the evening predicted serenity the next morning.…”
Section: The Jd-r Model and Its Association With Recovery Experiencesmentioning
confidence: 99%
“…Although the latter has advantages such as increasing perceived control over one's work (e.g., Mazmanian, Orlikowski, & Yates, 2013), it can also threaten an employee's physical and psychological wellbeing. Consequently, psychological detachment during out-ofwork hours has become more challenging for many, with mobile devices (such as Wi-Fi enabled laptops, tablets, and smartphones) contributing to semi-automatic responses that bypass conscious differentiation between ability to respond and obligation to do so (Barber & Jenkins, 2014;Derks, van Mierlo, & Schmitz, 2014;Porter & Kakabadse, 2006;Sonnentag, Binnewies, & Mojza, 2008). This development, together with the rise in the costs of living that is often unmatched with proportional growth in wages, is contributing to greater work intensification (Kakabadse, Kouzmin & Kakabadse, 2000).…”
Section: Introductionmentioning
confidence: 99%